2001
DOI: 10.1002/14651858.cd003393
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogens alone or with amniotomy for cervical ripening or induction of labour

Abstract: References to studies excluded from this review Gordon 1977 {published data only} Gordon AJ, Calder AA. Oestradiol applied locally to ripen the unfavourable cervix. Lancet 1977;2:1319-21. Gri in 2003 {published data only} Gri in C. Outpatient cervical ripening using sequential oestrogen-a randomised controlled pilot study [abstract].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…The local application of estrogen for the induction of labour has been tried,45 and estrogen does enhance cervical ripening 46. However, estrogens appear to be less effective than prostaglandins for the induction of labour and delivery, and there are insufficient data to draw any conclusions 47. The effect of estrogen alone on cervical ripening in postmenopausal women has not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…The local application of estrogen for the induction of labour has been tried,45 and estrogen does enhance cervical ripening 46. However, estrogens appear to be less effective than prostaglandins for the induction of labour and delivery, and there are insufficient data to draw any conclusions 47. The effect of estrogen alone on cervical ripening in postmenopausal women has not been investigated previously.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review determined the lack of data leading to definitive conclusions, nevertheless the studies analyzed do not indicate differences between women using estrogens for cervical ripening when compared to women using placebo. 18 The role of corticosteroids in the labor process is not well known yet. Classical experimental studies indicated the value of cortisol secretion by the fetal adrenal gland to the onset of parturition in lambs.…”
Section: Methods Of Cervix Ripeningmentioning
confidence: 99%
“…However, on a whole there were insufficient data to draw any conclusions regarding the efficacy of estrogen as an induction agent, given small, differing trials with different controls and different outcomes reported (86).…”
Section: Estrogenmentioning
confidence: 99%